HACE1 is a putative tumor suppressor gene in B-cell lymphomagenesis and is down-regulated by both deletion and epigenetic alterations. (June 2016) - Bouzelfen, Abdelilah; Alcantara, Marion; Kora, Hafid; Picquenot, Jean-Michel; Bertrand, Philippe; Cornic, Marie; Mareschal, Sylvain; Bohers, Elodie; Maingonnat, Catherine; Ruminy, Philippe; Adriouch, Sahil; Boyer, Olivier; et al.
Highlights: HACE1 expression in B-cell lymphoma tumors and cell lines was downregulated. Loss of HACE1 expression occurred through loss of heterozygosity and trough epigenetic mechanism. HDAC inhibitor could be sufficient to strongly reactivate the expression of HACE1. Down regulation of HACE1 expression may be involved in apoptosis and cell cycle arrest. HACE1 gene could be a potential target of epigenetic therapy in lymphoma. Abstract: HECT domain and ankyrin repeat containing E3 ubiquitin protein ligase 1, HACE1, located on chromosome 6q, encodes an E3 ubiquitin ligase and is downregulated in many human tumors. Here, we report HACE1 as a candidate tumor suppressor gene down-regulated by a combination of deletion and epigenetic mechanisms. HACE1 deletions were observed in 40% of B-cell lymphoma tumors. Hypermethylation of the HACE1 promoter CpG177 island was found in 60% (68/111) of cases and in all tested B-cell lymphoma lines. Using HDAC inhibitors, we observed predominantly inactive chromatin conformation (methylated H3 histones H3K9me2) in HACE1 gene promoter region. We demonstrated in Ramos and Raji cells that down-regulation of HACE1 expression was associated with a significant decrease in apoptosis and an accumulation of cells in the S and G2/M phases. Our experiments indicate that HACE1 can act as a haploinsufficient tumor suppressor gene in most B-cell lymphomas and can be downregulated by deacetylation of its promoter region chromatin, which makes HACE1 a potential target for HDAC inhibitors.